Bibliometric Analysis: Collaboration to Optimize Service Capacity to Inland Areas and Logistics Cost Efficiency Through Bundling Strategies and Inter-Port Cooperation - Faris Nofandi; Saut Gurning; Muhammad Saiful Hakim (International Journal of Marine Engineering Innovation and Research, 2025)
Optimizing logistics costs and service capacity is a critical focus in modern supply chain management, particularly for connecting ports to inland "hinterland" areas. This paper investigates how inter-port cooperation, strategic service bundling, and enhanced connectivity can improve logistics cost efficiency in these regions. The methodology combines an in-depth literature review with a bibliometric analysis using VOSviewer and Publish or Perish software. The literature review focuses on five key dimensions: hinterland connectivity, inter-port cooperation, cost efficiency, bundling strategies, and service improvement. The findings indicate that a strategic combination of inter-port collaboration and logistics service bundling significantly enhances logistics cost efficiency in the hinterland region. The bibliometric analysis also identifies key research clusters and highlights opportunities for future studies, particularly in under-researched regions like Indonesia, where green port implementation is underway. These findings have important implications for managers and policymakers in developing collaborative strategies to improve supply chain performance. The study concludes by proposing several hypotheses for future research concerning transportation costs, user priorities, and the performance of collaboration models.